(3MGTjI Ydi TQM GdTeSjIs - (3YeGO Hf jMji Hf Ydj GdbGQjs
(3ChdgG (B:s
(3ChdgG(B: (3bGd hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI, Cbhd(B: (3GYde Cf OCH GdeUfajf Cf jTjQhG aj Chd JUGfjage Edi CLRGFgG ELeGdG djchf GdTGQMs
(3BNQgG (B:s
(3BNQgG(B: (3hdG Tc Cf JUhQ GdCYe ef GdTjFjf hJUhQ GdNU ef GdTjFjf (B... (3Pdc GdTjA(B. (3bhdg(B: (3ShGA cGf eY GdJUhQs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs